An inventory of online reptile images - Marshall, Benjamin Michael; Freed, Paul; Vitt, Laurie J.; Bernardo, Pedro; Vogel, Gernot; Lotzkat, Sebastian; Franzen, Michael; Hallermann, Jakob; Sage, Richard D.; Bush, Brian; Duarte, Marcelo Ribeiro; Avila, Luciano Javier; et al. (Zootaxa, 2020)
No central online repository exists for the collection of animal images; hence it remains unclear how extensively species have been illustrated in the published literature or online. Here we compiled a list of more than 8000 reptile species (out of 11,341) that have photos in one of six popular online repositories, namely iNaturalist (6,349 species), the Reptile Database (5,144), Flickr (4,386), CalPhotos (3,071), Wikimedia (2,952), and Herpmapper (2,571). These sites have compiled over one million reptile photos, with some species represented by tens of thousands of images. Despite the number of images, many species have only one or a few images. This suggests that a considerable fraction of morphological and geographic variation is under documented or difficult to access. We highlight prominent gaps in amphisbaenians, lizards, and snakes, with geographic hotspots for species without images in Central Africa, Pacific Islands, and the Andes Mountains. We present a list of 3,000 species without photos in any of the six databases and ask the community to fill the gaps by depositing images on one of these sites (preferably with minimal copyright restrictions).